IMPLEMENTATION OF THE KUA REVITALIZATION PROGRAM IN THE SOUTHEAST PONTIANAK DISTRICT RELIGIOUS AFFAIRS OFFICE - surkiya, surkiya; Herawati, Netty; Pudjianto, S.Y. (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2024)
This research is entitled